Scenographies of Urban Desire. The display window as the border between reality and the ghostly space of desire in the 20’s Avant-garde cinema - Barreiro, Mª Soliña (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2014)
Display-windows and electric lights are capital in the set design of 20’s cinema. They defy material needs and night darkness; they foster an inconsumable desire night and day. The cinema of the 20s, especially Avant-garde cinema, filled up their images with glass, lights and merchandise, this feature can be analyzed as a critical metaphor of cinema itself. The screen as interactive membrane projects a kind of desire and lifestyle that are apparently achievable: mechanical image does not lie; it is transparent as the display-windows. But often fiction cinema fetishizes the social conditions of existence. This paper studies the display-window and cinema as an ephemeral urban set through 20’s film, texts and projects from an aesthetic and ideological point of view.
Keywords: display window; electric lights; Avant-garde cinema; fetishism; Berlin; Die Sinfonie der Grosstadt